(untitled) (Eurasian Medical Research Periodical, 2024)
Dysmetabolic nephropathy is a group of metabolic disorders in children in which structural and functional changes are observed in the kidneys. Almost always, the pathological process proceeds with crystalluria – the formation of salts in the urine. In the future, if left untreated, this condition can lead to the formation of urolithiasis. Pediatricians, nephrologists, urologists, with the participation of endocrinologists and other specialists, are engaged in the diagnosis and therapy of dysmetabolic nephropathy in childhood, as needed.